1976
DOI: 10.1007/bf00583647
|View full text |Cite
|
Sign up to set email alerts
|

Variability of cortical evoked responses in man related to slow wave activity

Abstract: Acoustically evoked responses were recorded from subdural and intracerebral electrodes chronically implanted in man. It was found that during slow wave activity especially the negative component at about 100 ms latency varies in form and amplitude. If the stimuli were presented during increasing cortical negativity, the amplitude of the 100 ms component of the evoked responses was generally larger than in the case of stimuli presented during decreasing negativity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Especially pertinent to the present study, it has been shown that evoked potentials can be modulated by the phase of an ongoing rhythm during which they are presented [for review and alternative viewpoint see Rudell (1980)]. For example, Pfurtscheller (1976) found that an ongoing slow oscillation rhythmically modulated the amplitude of N90 waves recorded from awake subjects.…”
Section: Variability and State-dependent Modulation Of Evoked Responsesmentioning
confidence: 81%
“…Especially pertinent to the present study, it has been shown that evoked potentials can be modulated by the phase of an ongoing rhythm during which they are presented [for review and alternative viewpoint see Rudell (1980)]. For example, Pfurtscheller (1976) found that an ongoing slow oscillation rhythmically modulated the amplitude of N90 waves recorded from awake subjects.…”
Section: Variability and State-dependent Modulation Of Evoked Responsesmentioning
confidence: 81%
“…Our findings bridge the gap between 2 emerging themes in systems neuroscience. On one hand, studies in a variety of disciplines including optical imaging, single-unit recording, and field potential/EEG recording have dramatically underscored the effects of ambient activity on sensory processing (Pfurtscheller 1976;Basar 1993a, 1993b;Steriade et al 1993;Arieli et al 1996;Contreras et al 1996;Polich 1997;Kisley and Gerstein 1999;Sanches-Vives and McCormick 2000;Truccolo et al 2002;Kruglikov and Schiff 2003;Fiser et al 2004;Lakatos et al 2005).…”
Section: Discussionmentioning
confidence: 99%